Study of Vehicle Weight-in-Motion System Based on Fiber-Optic Microbend Sensor - Ma Bin; Zou Xinguo (2010 International Conference on Intelligent Computation Technology and Automation, 2010)
In order to resolve the problem of electromagnetic interference and low precision in weight-in-motion (WIM) system, a WIM system based on the fiber-optic microbend sensor is proposed. The working principle of micro-bend fiber-optic sensor is discussed. The pressure on the sensor cause optical fiber deformed, which lead to the loss of output light, so the vehicle weight can be obtained through measuring the variation of light intensity in optical fiber. Photoelectric conversion and sampling circuits are designed, and wavelet transform is adopted to denoise the sampled signal. Static response experiment shows that the fiber-optic microbend WIM system has fine linear character to the pressure in the scope of 0-3000Kg. and its sensitivity is 3.8mV/Kg. Dynamic response experiments indicate that its measurement error is less than 5% when the vehicle velocity is under 15Km/h, which meet the requirement of weight in motion system very well.